Severity of Oral Mucositis in Children following Chemotherapy and Radiotherapy and Its Implications at a Single Oncology Centre in Durango State, Mexico - Ramón G. Carreón-Burciaga; Enrique Castañeda-Castaneira; Rogelio González-González; Nelly Molina-Frechero; Enrique Gaona; Ronell Bologna-Molina (Hindawi Limited, 2018)
Background. Mucositis is an adverse effect of chemotherapy (QT) and/or radiotherapy (RT). The purpose of this study was to investigate the occurrence of oral mucositis in children undergoing cancer treatment. Methods. Fifty-one children with cancer who had received QT, RT, or both (QT-RT) underwent clinical evaluations; World Health Organization criteria were used to establish the degree and severity of mucositis. The correlations between the clinical data, type of cancer, and therapy were statistically analysed. Results. Mucositis was present in 88.23% of the patients; 57.78%, 7.78%, and 24.44% received QT, RT, and QT-RT, respectively. Severity scores of 1 and 2 were the most common; scores of 3-4 were observed in patients who received QT-RT or more than 7 treatment cycles. There was a significant association between mucositis, the type of treatment, and the number of cycles received (p<0.05). Conclusion. It is important to implement therapeutic protocols that help maintain excellent oral health and reduce the risk of oral mucositis. Stomatologists should be consulted to assess patients' oral cavities and provide preventive treatment prior to QT and/or RT administration. It is important to integrate a stomatologist into the oncological working group to focus on preventing and managing oral mucositis.